2021
DOI: 10.1002/ece3.8225
|View full text |Cite
|
Sign up to set email alerts
|

Marine subsidy promotes spatial and dietary niche variation in an omnivore, the Keen’s mouse (Peromyscus keeni)

Abstract: Marine‐derived resource subsidies can generate intrapopulation variation in the behaviors and diets of terrestrial consumers. How omnivores respond, given their multiple trophic interactions, is not well understood. We sampled mice (Peromyscus keeni) and their food sources at five sites on three islands of the Central Coast of British Columbia, Canada, to test predictions regarding variation in the spatial behavior and consumption of marine‐subsidized foods among individuals. About 50% of detections (n = 27 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 144 publications
(190 reference statements)
1
7
0
Order By: Relevance
“…This hypothesis was also supported by our enrichment analyses, where, on smaller islands and closer to shore, we found enrichment of consumer 15 N without simultaneous enrichment of 13 C. Enrichment of consumer 15 N but not 13 C implies that the subsidy enriches soil, litter, and vegetation without direct consumption (Hocking & Reimchen, 2002). Similar conclusions were reached by a study on mouse diet variation on islands in our study area, where indirect effects of marine subsidies on mouse diets were observed through an increase δ 15 N of fecal pellets without a simultaneous increase in δ 13 C (Davidson et al, 2021). Due to the lack of a consistent pattern, we infer that variability in δ 13 C across taxa is likely driven by variability in plant δ 13 C. Plants obtain carbon from the atmosphere, but δ 13 C varies according to soil moisture, salinity, and nitrogen availability (Dawson et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This hypothesis was also supported by our enrichment analyses, where, on smaller islands and closer to shore, we found enrichment of consumer 15 N without simultaneous enrichment of 13 C. Enrichment of consumer 15 N but not 13 C implies that the subsidy enriches soil, litter, and vegetation without direct consumption (Hocking & Reimchen, 2002). Similar conclusions were reached by a study on mouse diet variation on islands in our study area, where indirect effects of marine subsidies on mouse diets were observed through an increase δ 15 N of fecal pellets without a simultaneous increase in δ 13 C (Davidson et al, 2021). Due to the lack of a consistent pattern, we infer that variability in δ 13 C across taxa is likely driven by variability in plant δ 13 C. Plants obtain carbon from the atmosphere, but δ 13 C varies according to soil moisture, salinity, and nitrogen availability (Dawson et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…To maximize the number of samples, we collected samples from a representative species or group of species from each trophic level that is common and abundant rather than species we explicitly know to be consumed by the next trophic level. Many of these samples were originally collected as discrete components of several separate projects under the umbrella of the "100 Islands Project" at the Hakai Institute (see Davidson et al, 2021;Nijland et al, 2017;Obrist et al, 2020;Wickham et al, 2019Wickham et al, , 2020. Additionally, due to the nature of small islands, we were unable to collect samples of every trophic level on every island.…”
Section: Field Collections and Measurementsmentioning
confidence: 99%
“…Dugan et al ., 2003 ; Schlacher et al ., 2017 ), it logically follows that this marine‐derived material may enhance the breeding success and productivity of these birds. Such bottom‐up control of populations is also likely for other mobile animals that assimilate nutrients from invertebrates associated with beach‐cast wrack, such as lizards (Barrett et al ., 2005 ; Spiller et al ., 2010 ), rodents, foxes, and bears (Ricci et al ., 1998 ; Stapp & Polis, 2003 ; Fox et al ., 2014 ; Davidson et al ., 2021 ; Page et al ., 2021 ) as well as feral pigs (M.A. Mateo & J.E.…”
Section: The Current State Of Knowledgementioning
confidence: 99%
“…These organisms attract secondary consumers as arthropods, polychaetes, birds, or fishes, forming a bottom-up food web largely based on the wrack (Dugan et al 2003;Hubbard and Dugan 2003;McLachlan and Brown 2006;Schlacher et al 2017). In turn, important vectors to nearshore terrestrial ecosystems such as dipterans and spiders use the wrack as a habitat and refuge (Olabarria et al 2007), which can be captured by omnivores such as mice or shorebirds (Obrist et al 2020;Davidson et al 2021). This fact affects the dynamics of the food web and is especially important when terrestrial productivity is low, for example during drought years (Anderson and Polis 1998).…”
Section: Introductionmentioning
confidence: 99%